Peran Refraksionis Optisien pada Pemeriksaan Mata di Bidang Hukum dalam Upaya Peningkatan Pelayanan Kesehatan Mata Masyarakat - Mochammad Kholil (stikes dharma husada bandung, 2020)
Optical Refraction Service is Optical / Optometric Refractionion is an integral part of health service, an important condition with increasing prevalence of refractive and eye disease, but still occurs Refraction Optisien does not implement standard of refractive optic service. The purpose of this study was to analyze the protection of optical patient's law in eye health service and the factors which become the reason of patient's dissatisfaction toward optical refractionion in eye health service in Semarang city. Research method is juridical normative empirical and the research specification used is descriptive analytical. Data used in this research is secondary data and primary data. Secondary data includes primary, secondary and tertiary legal materials, while primary data is obtained through field research (field Research). The result of the Research, it can be concluded that the illegal act done by Refractionist Optisien for not doing standard of refraction service due to lack of supervision and lack of knowledge about SOP about the legislation. The legal consequences for Optisien Refractionation that do not protect the optical patient are never implemented due to lack of supervision and guidance from Dinas Kesehatan. socialization to Optisien Refraksionis with the holding of seminars and workshops, and need sanction firmly against Refraction Optisien who do work not according to SOP